O uso de dispositivo multi-sensoriais para promoção do brincar em crianças com paralisia cerebral - Oliveira, Eliza Ribeiro de (2015)
The evolution in user interfaces has shown a strong trend in the use of tangible interfaces, in particular the tangible interfaces that promote a sensorial experience. The use of this type of resource can be interesting in different contexts, with the focus on scenarios where the sensory aspect is crucial to the interaction, as the performance of Assistive Technologies (AT). The purpose of this study is to investigate the effects of using multi-sensory devices for promoting the interaction in games for children with Cerebral Palsy (CP). CP refers to a series of clinical syndromes characterized by motor disorders and permanent postural changes which may or may not be associated with cognitive impairment and speech disorders. Because of the restricted motor condition, it is difficult the conduction of games for children with CP. This way, a motor delay can result in low play performance. This project is designed to approach the use of assistive technologies for providing a interactive game for children with CP. AT is used in order to provide independence and autonomy to people who show any dysfunction. For achieve the multi-sensory goal we are using a robotic ball called Sphero. The use of a robotic device enables to manipulate the ball remotely. This feature is very useful for children with physical disabilities. This way, Sphero was used as a part of the game, improving the movement sensations of the users. This study took place in the Department of Occupational Therapy at Federal University of Paraíba, where we offer a immersive games experience in a Occupational Therapy intevention.